2020
DOI: 10.1002/rra.3592
|View full text |Cite
|
Sign up to set email alerts
|

Sediment storage and shallow groundwater response to beaver dam analogues in the Colorado Front Range, USA

Abstract: Enthusiasm for using beaver dam analogues (BDAs) to restore incised channels and riparian corridors has been increasing. BDAs are expected to create a similar channel response to natural beaver dams by causing channel bed aggradation and overbank flow, which subsequently raise water tables and support vegetation growth. However, lack of funding for monitoring projects post‐restoration has limited research on whether BDAs actually cause expected channel change in the Front Range and elsewhere. Geomorphic and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 30 publications
0
29
3
Order By: Relevance
“…Although few field‐based studies of BDAs exist, the link between BDA height and function has been affirmed in other work. Scamardo and Wohl (2020) found that BDA height was a significant predictor of sedimentation volume associated with the structures. These findings provide further confirmation that ability of a BDA to alter riparian processes is closely linked to BDA size.…”
Section: Discussionmentioning
confidence: 99%
“…Although few field‐based studies of BDAs exist, the link between BDA height and function has been affirmed in other work. Scamardo and Wohl (2020) found that BDA height was a significant predictor of sedimentation volume associated with the structures. These findings provide further confirmation that ability of a BDA to alter riparian processes is closely linked to BDA size.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of natural beaver recolonisation, dam structures intended to mimic the form and function of beaver dams, called beaver dam analogues (BDAs), are used for restoring degraded streams. BDAs are low‐tech and inexpensive, constructed to be permeable instream structures made up of branches, mud and rock (Pilliod et al, 2018; Pollock, Lewallen, Woodruff, Jordan, & Castro, 2018; Scamardo & Wohl, 2020). There are three generic BDA designs that differ in structure, materials and desired outcomes (Pollock et al, 2018; Pollock, Wheaton, Bouwes, & Jordan, 2012), sometimes referred to as standard BDAs (Scamardo & Wohl, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…BDAs are low‐tech and inexpensive, constructed to be permeable instream structures made up of branches, mud and rock (Pilliod et al, 2018; Pollock, Lewallen, Woodruff, Jordan, & Castro, 2018; Scamardo & Wohl, 2020). There are three generic BDA designs that differ in structure, materials and desired outcomes (Pollock et al, 2018; Pollock, Wheaton, Bouwes, & Jordan, 2012), sometimes referred to as standard BDAs (Scamardo & Wohl, 2020). The types are: (a) starter dams—vertical posts with willow woven between the posts (wicker weave) and fill material (e.g., cobble, vegetation and mud) placed upstream, (b) post lines and wicker weave—just post lines with wicker weaves, which are highly permeable and (c) reinforced existing or abandoned natural beaver dams which involve simply reinforce existing or abandoned natural structures using vertical posts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations